2000
DOI: 10.15760/etd.2487
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Validation of a Group Theory Concept Inventory

Abstract: Within undergraduate mathematics education, there are few validated instruments designed for large-scale usage. The Group Concept Inventory (GCI) was created as an instrument to evaluate student conceptions related to introductory group theory topics. The inventory was created in three phases: domain analysis, question creation, and field-testing. The domain analysis phase included using an expert protocol to arrive at the topics to be assessed, analyzing curriculum, and reviewing literature. From this anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 92 publications
0
7
0
1
Order By: Relevance
“…Over the past 10 years, research into educational aspects of abstract algebra has gained increasingly more traction. With the works of Wasserman et al [1][2][3][4] and Melhuish [5][6][7], various studies have shown the benefits of learning abstract algebra and group theory in particular, as well as different pitfalls for students-an overview of the research results in this regard is presented in [8].…”
Section: Introduction 1literature Reviewmentioning
confidence: 99%
“…Over the past 10 years, research into educational aspects of abstract algebra has gained increasingly more traction. With the works of Wasserman et al [1][2][3][4] and Melhuish [5][6][7], various studies have shown the benefits of learning abstract algebra and group theory in particular, as well as different pitfalls for students-an overview of the research results in this regard is presented in [8].…”
Section: Introduction 1literature Reviewmentioning
confidence: 99%
“…In order to facilitate quantitative research into educational aspects of group theory and enrich findings from qualitative research (cf. Baldinger, 2018;Cook, 2018;Even, 2011;Suominen, 2018), two concept inventories have been developed in recent time: the GTCA (Group theory concept assessment) by Melhuish (2015) and the CI²GT (Concept inventory for introductory group theory) by Veith et al (2022b), respectively. Here, we conceive that conceptual understanding "reflects knowledge of concepts and linking relationships that are directly connected to (or logically necessitated by) the definition of a concept or meaning of a statement" (Melhuish, 2019, p. 2).…”
Section: Measuring Conceptual Understanding Of Group Theorymentioning
confidence: 99%
“…In recent years a body of research has emerged, entirely dedicated towards exploring educational aspects of abstract algebra (Wasserman, 2014(Wasserman, , 2016(Wasserman, , 2017(Wasserman, , 2018 and group theory in particular (Melhuish, 2015(Melhuish, , 2019Melhuish & Fagan, 2018;Pramasdyahsari, 2020;Veith & Bitzenbauer, 2022;Veith et al, 2022aVeith et al, , 2022bVeith et al, , 2022c. Even though group theory is mostly taught on university level mathematics, numerous connections to primary and secondary school mathematics have been uncovered (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Soyut olmanın yanı sıra soyut cebir kavramları, yüksek düzeyde karmaşık yani anlaşılması ve kullanılması için koordine edilmesi gereken birçok öğeyi (Melhuish, 2015) içinde barındıran kavramlardır. Melhuish'a (2015) göre bu durum APOS terminolojisinde şemalara karşılık gelmektedir.…”
Section: Tartışma Ve Sonuçlarunclassified